2017
DOI: 10.12973/eurasia.2017.00626a
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Technologies Trends in Education

Abstract: Virtual reality captures people's attention. This technology

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
195
1
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 360 publications
(212 citation statements)
references
References 19 publications
6
195
1
10
Order By: Relevance
“…First, while more advanced educational technology (e.g., virtual laboratory and other online simulation applications) has been employed in various disciplines of engineering education (see Martín‐Gutiérrez, Mora, Añorbe‐Díaz, & González‐Marrero, for a review), we found that engineering instructors using the flipped classroom approach usually provide video lectures, text‐based materials, and online quizzes to assess students' preclass understanding. Only Ghadiri et al () provided a virtual laboratory for students to create and observe their own simulations before class.…”
Section: Discussionmentioning
confidence: 99%
“…First, while more advanced educational technology (e.g., virtual laboratory and other online simulation applications) has been employed in various disciplines of engineering education (see Martín‐Gutiérrez, Mora, Añorbe‐Díaz, & González‐Marrero, for a review), we found that engineering instructors using the flipped classroom approach usually provide video lectures, text‐based materials, and online quizzes to assess students' preclass understanding. Only Ghadiri et al () provided a virtual laboratory for students to create and observe their own simulations before class.…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies which discuss the advantages and disadvantages of using AR in education . In ref.…”
Section: Introductionmentioning
confidence: 99%
“…One of the industry branches using the VR benefits to a great degree is the automotive branch [9]. The VR has also plenty of applications in medicine and biomedical engineering [10,11] and general education [12]. VR, as well as Augmented Reality (AR), plays an important role in Factories of the Future, within the Industry 4.0 concept [13,14].…”
Section: Introductionmentioning
confidence: 99%